2021
DOI: 10.1007/s42247-021-00188-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Conducting Polymers to Reduce Secondary Bacterial Infections among COVID-19 Patients: a Review

Abstract: The COVID-19 pandemic is a motivation for material scientists to search for functional materials with valuable properties to alleviate the risks associated with the coronavirus. The formulation of functional materials requires synergistic understanding on the properties of materials and mechanisms of virus transmission and disease progression, including secondary bacterial infections that are prevalent in COVID-19 patients. A viable candidate in the struggle against the pandemic is antimicrobial polymer, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 105 publications
2
24
0
Order By: Relevance
“…Altogether, this evidence shows that PPy-based NMs are promising candidates for future application in textiles or other antibacterial nanotechnologies, mainly thanks to their stability and biocompatibility to skin, which is the main target organ of surface coating NMs. Moreover, the data obtained give promising insights for the future research of PPy NPs for the spray coating of textiles with antiviral properties, also against SARS-Cov-2 as recently reported [ 37 ]. It has been indeed reported that conductive polymers are capable of binding different strains of viruses, including avian and influenza A and B human viruses, and that the functionalization of polymers with silver would increase the efficiency of virus adsorption, and almost complete the removal of viruses from aqueous media [ 38 ].…”
Section: Discussionsupporting
confidence: 54%
“…Altogether, this evidence shows that PPy-based NMs are promising candidates for future application in textiles or other antibacterial nanotechnologies, mainly thanks to their stability and biocompatibility to skin, which is the main target organ of surface coating NMs. Moreover, the data obtained give promising insights for the future research of PPy NPs for the spray coating of textiles with antiviral properties, also against SARS-Cov-2 as recently reported [ 37 ]. It has been indeed reported that conductive polymers are capable of binding different strains of viruses, including avian and influenza A and B human viruses, and that the functionalization of polymers with silver would increase the efficiency of virus adsorption, and almost complete the removal of viruses from aqueous media [ 38 ].…”
Section: Discussionsupporting
confidence: 54%
“…A recent study highlights the potential of CP coatings for personal protective equipment (PPE) and medical equipment to ward off secondary bacterial infections in hospital settings, given their current prevalence among COVID-19 patients. 550 CPs have been increasingly adopted for in vitro applications with bacterial cells given their innate or electrochemically induced antimicrobial properties as well as their ability to act as electron relays for bacterial extracellular electron transfer. The latter is of great importance not only for understanding and studying bacterial systems but also for developing energy generation/storage devices known as microbial fuel cells.…”
Section: Cell Membrane Modelsmentioning
confidence: 99%
“…In addition, CPs can also be used to replace alkaline metal as biosensors, such as for non-enzymatic glucose sensors, hydrogen peroxide (H 2 O 2 ) sensors, and dissolved oxygen sensors [ 107 ]. Recently, CPs like PANI was reported to have antibacterial properties through a disruption process against the native surface charge of bacterial cells [ 108 ]. This finding successfully proved that PANI can be utilized in producing antibacterial medical appliances.…”
Section: Current Developments Of Polymeric Materials For Biomedical Applicationsmentioning
confidence: 99%